United Kingdom : Financial Sector Assessment Program-Banking Supervision and Issues in Financial Stability. (IMF Staff Country Reports; Country Report, 2022)
The Financial Sector Assessment Program (FSAP) carried out a targeted evaluation of issues relating to the effectiveness of banking regulation and supervision in the United Kingdom. It leverages on the 2016 FSAP which concluded that the United Kingdom (U.K.) had a high degree of compliance with the 2012 Basel Core Principles (BCPs) with some shortcomings. The 2021 FSAP reviewed the progress in addressing them and examined the main supervisory and regulatory developments since the last FSAP. The FSAP evaluation also focuses on steps taken to minimize disruptions in the U.K. banking system at the end of the Brexit transition period, and on the regulatory and supervisory measures introduced to contain spillovers from the ongoing COVID-19 pandemic on the U.K. banking system.